Development and validation of the Adolescent Asthma Self-Efficacy Questionnaire (AASEQ). Issue 1 (4th July 2019) - Holley, Simone; Knibb, Rebecca; Latter, Sue; Liossi, Christina; Mitchell, Frances; Radley, Ruth; Roberts, Graham
Perceived self-efficacy is the belief that one can manage prospective situations. Good asthma self-management self-efficacy is associated with better asthma outcomes. However, a well-developed and validated tool to measure adolescent asthma self-management self-efficacy is lacking. Our objective was to develop and validate an Adolescent Asthma Self-Efficacy Questionnaire (AASEQ). The first stage of the study included a review of the literature, interviews with adolescents with asthma and consultations with parents and relevant healthcare professionals to develop a prototype scale. To assess reliability and validity, a further group of adolescents completed the prototype scale, the General Self-Efficacy Scale and KidCOPE (measures coping styles). Retesting was undertaken to assess longitudinal validity. Interviews with 28 adolescents and consultations with other stakeholders resulted in a 38-item prototype scale. Key themes were medication, symptom management, triggers, knowledge, attitude and beliefs around asthma, supportive relationships, schools and healthcare professionals. The prototype scale was completed by 243 adolescents. Factor and reliability analysis reduced it to a 27-item scale with four subsections: symptom management; medication; friends, family and school; and asthma beliefs. The 27-item scale had respectable to excellent internal consistency (α's 0.78–0.91) with results that were stable over time (intra-class correlation=0.82) in 63 subjects who completed it twice. Better adolescent asthma self-efficacy was associated with better general self-efficacy and indices of better asthma management. The AASEQ is a reliable and valid tool that is likely to aid future research and practice focused on adolescent asthma self-management and could be a useful intermediate outcome measure to assess the impact of behavioural interventions. The AASEQ is a reliable and valid tool that is likely to aid future understanding of adolescent asthma self-management and be a useful surrogate end-point to assess the impact of behavioural interventions. https://bit.ly/2DmL5KI